Education and economics : disciplinary evolution and policy discourse - Chattopadhyay, Saumen (New Delhi : Oxford University Press, 2013)
The title explores various conceptualisations of education in economic theory and how this has influenced policymaking in education. It deconstructs the interface between economic theory and education to unravel the role played by education in socio-economic development.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Economic development -- India; Education -- Economic aspects -- India; Education -- Social aspects -- India; Education and state -- India; India -- Economic policy -- 21st century